Creditors and Debtors’ Approval of the Transfer of Receivables (Cessie) is Reviewed in accordance with Law Number 10 of 1998 concerning Banking - Ikbal, Fikram; Alauddin, Rusdin; Suwarti (Jurnal Indonesia Sosial Sains, 2025)
This study discusses the transfer of receivables or cessies regulated in Article 613 of the Civil Code, focusing on the implementation and legal consequences in credit agreements in Indonesia. Cessie is the transfer of receivables from the old creditor to the new creditor, which must be done through an authentic deed or a deed under hand, and accompanied by a notice to the debtor to have a valid legal effect. Although regulated in the Civil Code, cessie practices are not always strictly regulated, and can cause legal conflicts if not carried out according to procedures. This study aims to explore the implementation of cessie in the banking sector, as well as the legal impact arising from the transfer of receivables on the rights and obligations of debtors and creditors. The results of the study show that the legal transfer of receivables can only be done if it is in accordance with applicable regulations and the debtor is given a notice or written consent regarding the transfer. The study also suggests the need for further arrangements regarding cessies to ensure legal protection for all parties involved in the transaction.